2019
DOI: 10.1126/sciadv.aat5752
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic continental moisture gradient drove Amazonian bird diversification

Abstract: The Amazon is the primary source of Neotropical diversity and a nexus for discussions on processes that drive biotic diversification. Biogeographers have focused on the roles of rivers and Pleistocene climate change in explaining high rates of speciation. We combine phylogeographic and niche-based paleodistributional projections for 23 upland terra firme forest bird lineages from across the Amazon to derive a new model of regional biological diversification. We found that climate-driven refugial dynamics inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
186
3
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 138 publications
(218 citation statements)
references
References 64 publications
22
186
3
7
Order By: Relevance
“…By contrast, the BSP and EBSP analyses found some evidence that the majority of the L. coronata subclades underwent a more recent demographic expansion, between 50,000 and 10,000 years before present, which is compatible with the evidence of demographic fluctuations resulting from the shifts in climate that occurred during the Pleistocene, as in Haffer's (2008) refugia model. These findings are also consistent with the results of other studies of Amazonian birds that inhabit terra firme forests, which have also revealed a tendency for recent demographic fluctuations that have possibly resulted from changes in forest cover and associated oscillations in the availability of resources that occurred during the Pleistocene (d' Horta et al, 2013;Fernandes et al, 2012;Harvey & Brumfield, 2015;Ribas et al, 2012;Silva et al, 2019;Thom & Aleixo, 2015). Furthermore, the lack of any evidence of the potential role of the Negro River as a primary barrier reinforces the probable influence of climatic processes in the recent diversification of certain L. coronata groups.…”
Section: Biogeographic Events and The Diversification Of The Lepidosupporting
confidence: 91%
“…By contrast, the BSP and EBSP analyses found some evidence that the majority of the L. coronata subclades underwent a more recent demographic expansion, between 50,000 and 10,000 years before present, which is compatible with the evidence of demographic fluctuations resulting from the shifts in climate that occurred during the Pleistocene, as in Haffer's (2008) refugia model. These findings are also consistent with the results of other studies of Amazonian birds that inhabit terra firme forests, which have also revealed a tendency for recent demographic fluctuations that have possibly resulted from changes in forest cover and associated oscillations in the availability of resources that occurred during the Pleistocene (d' Horta et al, 2013;Fernandes et al, 2012;Harvey & Brumfield, 2015;Ribas et al, 2012;Silva et al, 2019;Thom & Aleixo, 2015). Furthermore, the lack of any evidence of the potential role of the Negro River as a primary barrier reinforces the probable influence of climatic processes in the recent diversification of certain L. coronata groups.…”
Section: Biogeographic Events and The Diversification Of The Lepidosupporting
confidence: 91%
“…Patterns of taxonomic and phylogenetic beta diversity in Amazonia were strongly congruent, indicating that relatively recent evolutionary and/or ecological processes are more important for the structure of bird communities in Amazonia than old evolutionary processes (i.e. diversification at the base of the phylogeny; Hattab et al , Silva et al ). These processes are likely associated with the presence of dispersal barriers and environmental filters, even though Passeriformes have an evident ability to disperse longer distances than other terrestrial vertebrates.…”
Section: Discussionmentioning
confidence: 97%
“…In tropical regions, large rivers might act as barriers to species dispersal leading to differences in community composition across river margins (Cracraft , Hayes and Sewlal , Pomara et al , Naka and Brumfield , Silva et al ). Limited dispersal can promote allopatric speciation (Ribas et al ) or prevent secondary contact of extant species (Naka and Brumfield ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations